Subdivision of the genus Gluconacetobacter Yamada, Hoshino and Ishikawa 1998: The proposal of Komagatabacter gen. nov., for strains accommodated to the Gluconacetobacter xylinus group in the α-Proteobacteria - Yamada, Yuzo; Yukphan, Pattaraporn; Vu, Huong Thi Lan; Muramatsu, Yuki; Ochaikul, Duangjai; Nakagawa, Yasuyoshi (My University, 2012)
The genus Gluconacetobacter is divided into two groups phylogenetically, phenotypically and ecologically: the Gluconacetobacter liquefaciens group and the Gluconacetobacter xylinus group. For the latter group, the genus Komagatabacter is newly introduced, and the type species of the new genus is designated as Komagatabacter xylinus (Brown 1886) comb. nov. Twelve species of the Gluconacetobacter xylinus group are transferred to the new genus as new combinations. © Springer-Verlag and the University of Milan 2011.
Keywords: Acetic acid bacteria; Acetobacteraceae; Gluconacetobacter; Komagatabacter gen. nov.; Komagatabacter xylinus comb. nov.